Psicologia e inclusão escolar: novas possibilidades de intervir preventivamente sobre problemas comportamentais - Silva, Aline Maira da (Universidade Federal de São Carlos, 2010)
Expectations on inclusive education have demanded the creation of new staff roles in schools. In an inclusive school environment, an important aspect of the role of educational psychologists that seems to be a promising picture in this profession is to promote and develop strategies and guidelines for consideration and adoption of the Collaborative Consultation in the Schools, building partnership with teachers and families. The aim of this study was to evaluate the effects of a preventive intervention program, based in the principles of the Collaborative Consultation in Schools and the Positive Behavior Support models, designed to prevent and minimize behavior problems. The study has been conducted in three 1st. grade classrooms in a public elementary school located within the state of São Paulo, assessing three teachers of these classrooms, fifty-five pupils, and eighteen families participation. The study has been carried out in four phases. In Phase 1, the ethical procedures were followed to contact the school. In Phase 2 at the pre-test stage, participating families were asked to complete the Parenting Styles Inventory (PSI) instruments as well as the teachers were requested to complete the Child and Youth Behavior Inventory (6-18 years)/Teacher Report Form (TRF). In Phase 3, the preventive intervention program was implemented, targeting and focusing on teachers, pupils, and participating families. Finally, in Phase 4, at post-test stage, both instruments were repeated and moreover individual focal groups meetings were held with teachers and families in order to examine the social validity of the study as well as it was gathered qualitative data to analyze the effects of the previously applied intervention program. To assess the impact of the intervention, MANOVA test was applied to the results obtained with the PSI and the TRF. Regarding parenting styles, there was a statistically significant increase in the parenting style index, with respect to the positive monitoring and moral behavior, and a statistically significant decrease in relaxed discipline, and in the negative monitoring. In relation to student behavior, according to reports from teachers, there was a statistically significant decrease either in internalizing or externalizing problems, or in total problems. The results of the focal group meetings held with the families provided information about favorable and unfavorable aspects of the intervention; it was noticed positive changes in child and family behavior; it was evaluated the position of a psychologist within the school. Finally, the meetings with the teachers allowed to gather information about the characteristics of the collaboration that were included in the developed intervention; favorable and unfavorable aspects of the intervention; positive changes related to student behavior at school and their quality of life; degree of applicability of the developed strategies; evaluation of the position of a psychologist at the school.
Keywords: Educação especial - inclusão; Consultoria colaborativa; Suporte comportamental positivo; Problemas de comportamento; Psicologia escolar; Inclusão escolar; Collaborative consultation in the school; Positive behavior support; Behavior problems; School inclusion; School Psychology; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL